'They go to get a gun': Hidden histories of violence and the politics of rumour in Israel. (December 2016) - McGahern, Una
This article examines rumour as a distinct type of speech act and makes a case for engaging with the spaces within which rumours are deployed and circulated in practice. Critiquing the rigid linguistic focus on speech acts within prevailing securitization theories, it follows insights from the fields of political geography and anthropology in order to incorporate voices from the margins more fully into its analysis of threat construction. Examining the local deployment and circulation of rumours in religiously mixed Arab localities in Israel, it argues that the perlocutionary force of rumour not only is rooted in local security and policing arrangements but reveals a spatialization of violence that is particular to the margins. In so doing, the article seeks to contribute to a broadening of the research agenda on the social construction of threat that would not only bring 'security have-nots' to the centre of its analysis but draw attention to the margins as a particular type of security space.